State and Trends of the Carbon Market 2008 - Capoor, Karan (World Bank, Washington, DC, 2013)
The carbon market is the most visible result of early regulatory efforts to mitigate climate change. Regulation constraining carbon emissions has spawned an emerging carbon market that was valued at US$64 billion (Euro 47 billion) in 2007. Its biggest success so far has been to send market signals for the price of mitigating carbon emissions. This, in turn, has stimulated innovation and carbon abatement worldwide, as motivated individuals, communities, companies and governments have cooperated to reduce emissions. The European Union Emission Trading Scheme (EU ETS) market has been successful in its mission of reducing emissions through internal abatement at home, and of stimulating emission reductions abroad. The European Commission, learning from the experience of Phase I, has strengthened several important design elements for EU ETS Phase II. Clean Development Mechanism (CDM) accounted for the vast majority of project-based transactions (at 87 percent of volumes and 91percent of values) and JI saw transacted volumes doubling and values tripling in 2007 over the previous year. The CDM alone saw primary transactions worth US$7.4 billion (Euro 5.4 billion), with demand coming mainly from private sector entities in the EU, but also from EU governments and Japan.